Gene Signatures Detect Damaged Liver Sinusoidal Endothelial Cells in Chronic Liver Diseases - Verhulst, Stefaan; van Os, Elise Anne; De Smet, Vincent; Eysackers, Nathalie; Mannaerts, Inge; van Grunsven, Leo A. (Frontiers in Medicine, 2021)
Liver sinusoidal endothelial cells have a gatekeeper function in liver homeostasis by permitting substrates from the bloodstream into the space of Disse and regulating hepatic stellate cell activation status. Maintenance of LSEC’s highly specialized phenotype is crucial for liver homeostasis. During liver fibrosis and cirrhosis, LSEC phenotype and functions are lost by processes known as capillarization and LSEC dysfunction. LSEC capillarization can be demonstrated by the loss of fenestrae (cytoplasmic pores) and the manifestation of a basement membrane. Currently, no protein or genetic markers can clearly distinguish healthy from damaged LSECs in acute or chronic liver disease. Single cell (sc)RNA sequencing efforts have identified several LSEC populations in mouse models for liver disease and in human cirrhotic livers. Still, there are no clearly defined genesets that can identify LSECs or dysfunctional LSEC populations in transcriptome data. Here, we developed genesets that are enriched in healthy and damaged LSECs which correlated very strongly with healthy and early stage- versus advanced human liver diseases. A damaged LSEC signature comprised of Fabp4/5 and Vwf/a1 was established which could efficiently identify damaged endothelial cells in single cell RNA-seq data sets. In LSECs from an acute CCl4 liver injury mouse model, Fabp4/5 and Vwf/a1 expression is induced within 1-3 days while in cirrhotic human livers these 4 genes are highly enriched in damaged LSECs. In conclusion, our newly developed gene signature of damaged LSECs can be applicable to a wide range of liver disease aetiologies, implicating a common transcriptional alteration mechanism in LSEC damage.